The Jamontt Family in the 1863–1864 Uprising and Konstanty Kalinowski’s “Letters from beneath the Gallows” - Bairašauskaitė, Tamara (Lietuvos istorijos studijos, 2025)
This article presents a discussion of the Jamontt family’s role in the 1863–1864 Uprising and attempts to offer a new reading of Konstanty Kalinowski’s “Letters from beneath the Gallows”. The main source used in this research were the memoirs of Ludwika Jamontt-Rodziewicz (1836–1914), along with material from the Vilnius political cases interrogation commissions and related historiography. Members of the Jamontt family, primarily the author of these memoirs, her husband, her brother Józef and three sisters, including Kalinowski’s fiancée Maria, their relatives and friends were assistants in the Lithuanian executive department, led by Kalinowski. The article pays attention to the biographies of this family’s members and their participation in the creation of a network of assistants to the leader of the uprising. The location of the Jamontt apartment in Vilnius, which became the center of Kalinowski’s activities, was also determined.On account of the timing of when Kalinowski wrote his “Letters from beneath the Gallows”, interpretations of their content can be considered as polemizing with the ideological significance attributed to them in Belarusian historiography and the attempts by the Russian propagandist, historian Aleksandr Dyukov to belittle their ideological and political aspects. Dyukov insists that while imprisoned, Kalinowski wrote only letters to his fiancée in Polish. Kalinowski’s letter to Maria Jamontt, written just before his execution, is published in the article. An analysis of Agaton Giller’s published “Letters from beneath the Gallows” and the so-called “explanation” attached to Kalinowski’s interrogation file shows that in these documents, the leader of the uprising expressed his political views, his thoughts about the fate of the uprising and the country’s future, though they cannot be said to invoke the Belarusian national idea.